A Comparative Clinicopathological Study on Powder of Aegle marmelos Leaf and Withania coagulans Flower in the Management of Madhumeha - Swain, Sangram Keshari; Nayak, Utkalini; Panda, Pradip Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Background: In view of Ayurveda, abnormal and profuse excretion of urine in general is called as Prameha. If we do not treat the Prameha, it leads to Madhumeha. There are many herbs mentioned in Ayurveda that have Madhumehahara property. Hence, to control Madhumeha two effective Ayurvedic drugs, namely, “Aegle marmelos” and “Withania coagulans” were selected for the present study. The study aimed to study the efficacy of A. marmelos leaf and W. coagulans flower powder in the management of Madhumeha. Materials and Methods: For the present study, 40 patients of Madhumeha were randomly selected according to the Inclusion criteria. The prepared medicine was trailed in two groups (Groups A and B) each having 20 Patients. The assessment was in every 10 days of intervals. Discussion and Conclusion: Statistically, A. marmelos leaf powder provided no significant results and W. coagulans flower powder provided significant results in improving subjective and objective signs and symptoms of Madhumeha.